Compressive strength of 3D printing bio-composites mortar - Ismail, Nur Amira Natasha; Ibrahim, Mustaffa; Abdullah, Radziah (AIP conference proceedings, 2023)
Kenaf is a part of natural fibers that has been subject of interest for research in the past few decades because of its advantages which is lightweight, cheap, abundantly available and a good alternative to substitute the using of synthetic fiber. The aim for this paper is to explore the effect of using kenaf powder on the initial compressive strength of 3D printing mortar. The addition of the kenaf powder as a bio-composites material in the cement mortar with a variance weight and water addition also assessed to test the effect of compressive strength. Kenaf powder with 0%, 30%, 40% and 50% (by weight of cement) with size passing through 150µm were used to produce 50mm x 50mm x50mm of cube specimen. The 3D printing mortar cubes were air curing for 7 days before testing to the machine. A total of 24 cubes were used for this study. INSTRON universal machine is used to testing the cubes. Experiment results revealed that due to high amount of kenaf powder added gradually into the mixer samples, the compressive strength values obtained were lower when compared to the plain mortar. Based on the conclusion made, K50W650 shows a favorable result where the value of the compressive strength was highest among others.